2016
DOI: 10.4236/oje.2016.61002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biodiesel Production from African Crude Palm Oil (<i>Elaeis guineensis</i> Jacq) with High Concentration of Free Fatty Acids by a Two-Step Transesterification Process

Abstract: In this study, African crude palm olein (CPO) was used to synthesize biodiesel. The objective was to determine the optimal reaction conditions for the methanolysis of olein. The used CPO had a 5.72% concentration of free fatty acids (FFA); thus, the production of biodiesel was carried out in two stages: 1) esterification using sulfuric acid and 2) transesterification using sodium methoxide. In order to optimize the yield of biodiesel during the transesterification process, a central rotatable design and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Generally, the content of FFAs in tobacco seeds is approximately 6% ( Stanisavljević et al, 2007a ). This high level would result in saponification and then the difficulty in transesterification because the FFA level exceeds 2% ( Anguebes-Franseschi et al, 2016 ). To decrease acid levels, pre-esterification with homogeneous acid could be performed.…”
Section: Transesterification Of Biodiesel In Tobacco Seed Oilmentioning
confidence: 99%
“…Generally, the content of FFAs in tobacco seeds is approximately 6% ( Stanisavljević et al, 2007a ). This high level would result in saponification and then the difficulty in transesterification because the FFA level exceeds 2% ( Anguebes-Franseschi et al, 2016 ). To decrease acid levels, pre-esterification with homogeneous acid could be performed.…”
Section: Transesterification Of Biodiesel In Tobacco Seed Oilmentioning
confidence: 99%
“…Some authors, such as Ali and Tay (2013) and Feroldi et al (2014), found the optimal conditions for palm oil biodiesel production using methanol in the transesterification process: the methanol:oil molar ratio of 6:1, reaction time of 60 minutes and temperature of 60°C with 1% of KOH as a catalyst, resulting in 88% yield. Likewise, Anguebes-Franseschi et al (2016) obtained a yield of 90% in palm oil biodiesel production with a reaction temperature of 56°C, 135 minutes, and a NaOH catalyst proportion of 0.65%.…”
Section: Introductionmentioning
confidence: 95%
“…Different studies carried out by Ali and Tay (2013), Sukjit andPunsuvon (2013), Feroldi et al (2014), Wong et al (2015), Anguebes-Franseschi et al (2016), among others, analysed the variables associated with the biodiesel production from palm oil, and found that the molar ratio ethanol:oil, temperature and stirring time are the most important factors involved in the reaction. Some authors, such as Ali and Tay (2013) and Feroldi et al (2014), found the optimal conditions for palm oil biodiesel production using methanol in the transesterification process: the methanol:oil molar ratio of 6:1, reaction time of 60 minutes and temperature of 60°C with 1% of KOH as a catalyst, resulting in 88% yield.…”
Section: Introductionmentioning
confidence: 99%
“…The basic condition catalyst will occur reaction with free fatty acids and reduce the yield of the ester production. Acid condition is more suitable for oils or fats with high fatty acid content [8]. Esterification reaction that uses basic catalysts is more suitable for oils with high purity, and is not suitable for oils with high fatty acid content, such as rice bran oil with high free fatty acid content.…”
Section: Introductionmentioning
confidence: 99%